REPRODUCTIVE STRATEGY OF THE BLUE CRAB Callinectes sapidus RATHBUN, 1896 (DECAPODA, BRACHYURA, PORTUNIDAE), IN ROCHA LAGOON, URUGUAY (Boletín de la Sociedad Zoológica del Uruguay, 2025)
Callinectes sapidus Rathbun, 1896, is artisanal caught in the coastal lagoon system from Uruguay to Brazil. To analyze their reproductive strategy, 422 individuals were extracted from Laguna de Rocha (34°33'S, 54°22'W), which were sexed, measured and dissected. The mean size (CWm) differed significantly between the seasons (H= 66,37; p
Keywords: Callinectes; Decapoda; reproduction; Racha Lagoon